Enciklopedija slovenske kulturne zgodovine na Koroškem – nekaj misli znanstvenega urednika ob njenem izidu Enzyklopädie der slowenischen Kulturgeschichte in Kärnten/Koroška, Von den Anfängen bis 1942 – Überlegungen des wissenschaftlichen Redakteurs anlässlich ihrer Publikation - Schnabl, Bojan Ilija (Studia mythologica Slavica, 2016)
Encyclopedia of the Slovenian Cultural History in Carinthia, From Early Times to 1942 – Thoughts of its Scientific Editor on the Occasion of its Publishing. The Encyclopedia of the Slovenian Cultural History in Carinthia, published by Katja Sturm-Schnabl and Bojan-Ilija Schnabl, is a modern genuine interdisciplinary and intercultural scientific research work on regional Slovenian and intercultural processes in Carinthia (Austria) published in German language. It is consideret as a “magnum opus” which strives to be a contribution to the European scientific discourse. The Encyclopedia has over 1000 entries of more than 160 authors from different scientific backgrounds (from Austria, Slovenia, Italy, Germany, France, Russia and the USA). Specific perspectives and focuses provide new, relevant scientific findings. Its structured form gives on one hand an easy access to single research findings while at the same time reveals additional meta-levels and further dimensions of knowledge.